The Effect of Cinematherapy-Based Group Reminiscence on Older Adults’ Self Esteem - Intan Maharani Sulistyawati Batubara; Niken Yuniar Sari; Megan Eagle (GLOBAL HEALTH SCIENCE GROUP, 2020)
Self-esteem tends to be stable throughout the lifespan. Yet, changes in the aging process cause multiple factors to affect problematic self-esteem, which later cause older adults to endure loss. Cinematherapy-based reminiscence group therapy is a strategic intervention in increasing self-esteem. The purpose of this research was to identify the effects of cinematherapy-based reminiscence group therapy for self-esteem in older adults. The design of this research was quasi-experimental design including pre-posttest with the control group. Samples were selected with a total sampling technique that met the inclusion criteria. Subjects were 70 respondents consisting of 35 each group, obtained by a simple random sampling technique. The nursing intervention was provided to the control group, while cinematherapy-based reminiscence group therapy was provided to the treatment group. This research used reminiscence therapy workbook. The measurement of self-esteem in older adults was done by using Rosenberg’s Self-Esteem. A paired t-test and independent t-test performed the analysis. The result of the research showed that self-esteem levels increased significantly in both control and treatment groups. In contrast, the treatment group’s increase in self-esteem indicated a higher number than the control group. A combined cinematherapy-based reminiscence group therapy helps use a movie to bring positive feelings and reminisce memorable past stories. In addition, as a group program, cinematherapy-based reminiscence group therapy improves communications and builds a sense of belonging to the community. Cinematherapy-based reminiscence group therapy is recommended to increase self-esteem in older adults at nursing home.